Recovery of outer retinal laminations on optical coherence tomography after treatment of cancer associated retinopathy - Francisco J. Irizarry; Laura J. Kopplin; Sherveen S. Salek; Grazyna Adamus; Mohamed Saleh; Kristin Biggee; Phoebe Lin; James T. Rosenbaum (American Journal of Ophthalmology Case Reports, 2017)
Purpose: To report novel optical coherence tomography findings in a case of anti-α-enolase cancer associated retinopathy. Observations: An elderly female presented with bilateral decreased vision and a recent diagnosis of ovarian carcinoma. Optical coherence tomography demonstrated bilateral loss of outer retinal structures and macular edema. Serum testing found antibodies against α-enolase and 82–84 kDa proteins. Outer retinal structures showed recovery, macular edema resolved and repeat anti-retinal antibody testing became negative following cancer therapy and topical difluprednate treatment. Conclusions and importance: Cancer associated retinopathy is a paraneoplastic disease that results in damage to retinal structures through an autoimmune response. The damage is generally considered to be irreversible; however, in rare cases, such as observed here, retinal structures may demonstrate recovery after treatment.